ASK AND CLARIFY ABOUT STUDENT SHARING OF THE CONCEPT OF REFLECTION - Buhaerah, Buhaerah Buhaerah; Haq, Muhammad Ahsanul; Nurfaizah, Nurfaizah (FKIP Universitas Muhammadiyah Tangerang, 2024)
While studying mathematics in tertiary institutions, students must understand basic mathematics concepts. One of the main subjects in the mathematics education study program is transformation geometry. One of the materials in this course is the concept of reflection. In the reflection concept material, students remember mathematical formulas and know how to solve problems. Learning through sensitive questions and clarification is learning through a shared learning strategy that focuses on two characteristics. In this lesson, students ask questions and or answers. Students form small groups, and each group explains when there are questions. Discussions and interviews were carried out on behalf of each group. Students present the results of the survey and clarification in class. Ask students to clarify if there are questions that are ambiguous or wrong. In this study, the lecturer only acts as a facilitator.